Analisis CP, Penyusunan CP Menjadi TP, TP Menjadi ATP, dan Pembelajaran Berdiferensiasi Di SDIT Babul Huda Siak Hulu - Inayah Pama, Violeta; Fitri, Anggi; Sari, Meiliza; Khasanah, Niswatul; Zalisman, Zalisman; Maspuri, Maspuri; Abidin, Zaitun (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
The objective of the Training on CP Analysis, Transforming CP into TP, TP into ATP, and Differentiated Learning at SDIT Babul Huda is to enhance teachers' understanding in designing lesson plans that align with the current curriculum, thereby making the classroom learning process more effective. Additionally, this training aids teachers in comprehending how to implement differentiated learning, which can offer flexibility and increase student engagement in their studies. This activity was attended by 24 teachers from SDIT Babul Huda Siak Hulu. The results of this community service activity indicate that the participants were able to analyze and compose CP, TP, ATP accurately, and they also gained an understanding of how to effectively and appropriately apply differentiated learning